ПЕРСИСТИРУЮЩИЕ ИДИОПАТИЧЕСКИЕ ЛИЦЕВЫЕ БОЛИ С ПОЗИЦИИ ПСИХОСОМАТИЧЕСКОЙ МЕДИЦИНЫ - В. Э. Медведев; Ю. С. Фофанова; В. И. Фролова (SINAPS LLC, 2015)
Prosopalgia is the subtype of chronic facial pain. It is not associated with any local pathologic process. Pain syndrome manifests in connection with emotional stress and is comorbid to heterogenic mental disorders. The most effective treatment strategies include different psychotropic drugs and psychotherapy. Taking into consideration important medical and social aspects of this subtype of facial pain complex treatment strategy is necessary with he participation of psychiatrist.